Impact of an Acceptance Facilitating Intervention on Patients' Acceptance of Internet-based Pain Interventions. Issue 6 (June 2015) - Baumeister, Harald; Seifferth, Holger; Lin, Jiaxi; Nowoczin, Lisa; Lüking, Marianne; Ebert, David
<x xml:space="preserve">Abstract</x> Objective: Results from clinical trials indicate that Internet-based psychological pain interventions are effective in treating chronic pain. However, little is known about patients' acceptance of these programs and how to positively influence patients' intention to engage in them. Therefore, the present study aimed (1) to assess patients' acceptance of Internet-based interventions, and (2) to examine whether patients' acceptance can be increased by an acceptance facilitating intervention. Methods: A total of 104 patients with chronic pain from 2 pain units were randomly allocated to an intervention group (IG) and a no-intervention control group (CG). The IG was shown a short informational video about Internet-based psychological pain interventions before receiving a questionnaire on patients' acceptance of Internet-based psychological pain interventions and predictors of acceptance (performance expectancy, effort expectancy, social influence, facilitating conditions, Internet usage, and Internet anxiety). The CG filled out the questionnaire immediately. Patients' acceptance was measured with a 4-item scale (sum score ranging from 4 to 20). Results: Baseline acceptance of Internet-based interventions was reported as low (sum-score:4-9) by 53.8%, moderate (10 to 15) by 42.3%, and high (16 to 20) by 3.9% of the patients with chronic pain in the CG. The IG showed a significantly higher acceptance (M=12.17, SD=4.22) than the CG (M=8.94, SD=3.71) with a standardized mean difference of d=0.81 (95% CI, 0.41, 1.21). All predictor variables were significantly improved in the IG compared with the CG, except for Internet usage. Conclusions: Patients with chronic pain display a relatively low acceptance of Internet-based psychological pain interventions, which can be substantially increased by a short informational video.